Efecto de las descargas de aguas residuales de la empresa EMSABA EP sobre la calidad del agua del rio Babahoyo año 2018 - Sandal Paucar, Mariano Salomón (2019)
In recent years the water quality in the Babahoyo area has decreased due to the discharges of wastewater of all kinds, in addition to the existence of contamination of natural origin, for this reason the present investigation evaluated the physical-chemical parameters that characterize the river Babahoyo ranges of variation and variables that most influence the quality of water. This study was carried out during the months of January to March of 2019, samplings were made in the Babahoyo river in three different points; before, on the site and after the discharge of wastewater; In the process parameters such as pH, temperature and conductivity were measured in situ, in the same way the samples were conserved and preserved to determine physical-chemical parameters such as alkalinity, BOD5, COD, sulphates, nitrites, phosphate, suspended solids, total solids , fats and oils, total coliforms and fecal coliforms, CO2 and H2S. Based on the analyzed parameters, the pollution indices by mineralization, organic matter and suspended solids were evaluated. There was a low contamination index in the sampling site corresponding to the previous one, index of average contamination in the sampling site of the discharge, high pollution index in sampling site after discharge. Of all the parameters analyzed, those that exceeded the maximum permissible limits in the three sampling points were suspended solids, total coliforms and fecal coliforms. The concentrations found and the impacts generated by the discharge of direct residual water to the water resource are of concern, the other parameters they are within the maximum permissible limits, in comparison with the provisions of the Unified Text of Secondary Legislation of the Ministry of the Environment (TULSMA). Passwords: water quality, quality indexes, contamination, physical-chemical parameters, water resources and discharge of residual wate